Association between sarcopenia and the prevalence of depression among community-dwelling older adults - Robiatun Amaliyah Ranti; Sudijanto Kamso; Ali Nina Liche Seniati; Purwanty Astuti Ascobat (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Depression is a common mental health issue among older adults, especially those living in nursing homes, and sarcopenia is suspected to be a contributing factor. This study aimed to explore the association between sarcopenia and depressive symptoms in elderly residents of social care institutions in Jakarta. Methods: A descriptive–correlational study with a quantitative approach was conducted. A total of 422 older adults were randomly selected from 1,168 residents of Panti Sosial Tresna Werdha Budi Mulia. Inclusion criteria were willingness to participate, ability to speak Indonesian, residence in the institution, and age ≥60 years. Residents hospitalized during data collection or who declined participation were excluded. Data were collected using the Geriatric Depression Scale (GDS-15) and validated instruments assessing psychosocial status, cognition, sleep quality, physical activity, and sarcopenia markers based on AWGS criteria. Statistical analysis was performed using the Chi-square test, with significance set at p < 0.05. Results: Depressive symptoms were strongly associated with sarcopenia. Older adults with sarcopenia were nearly twice as likely to experience depression as those without (OR = 2.02; 95% CI: 1.35–3.03; p = 0.001). Reduced muscle strength, limited mobility, and social withdrawal may increase vulnerability to depression. Conclusion: Among institutionalized older adults, sarcopenia is a strong predictor of depressive symptoms. These findings highlight the importance of early screening and integrated interventions including physical rehabilitation, nutritional support, and psychosocial programs to reduce depression and improve overall well-being.